Report from the European Society of Thoracic Surgeons prospective thymic database 2017: a powerful resource for a collaborative global effort to manage thymic tumours. (10th January 2019) - Ruffini, Enrico; Guerrera, Francesco; Brunelli, Alessandro; Passani, Stefano; Pellicano, Danilo; Thomas, Pascal; Van Raemdonck, Dirk; Rocco, Gaetano; Venuta, Federico; Weder, Walter; Detterbeck, Frank; Falcoz, Pierre-Emmanuel
Abstract: OBJECTIVES: We queried the European Society of Thoracic Surgeons (ESTS) prospective thymic database for descriptive analysis and for comparison with the ESTS retrospective thymic database (1990–2010). METHODS: Data were retrieved (January 2007–November 2017) for 1122 patients from 75 ESTS institutions. RESULTS: There were 484 (65%) thymomas, 207 (28%) thymic carcinomas and 49 (7%) neuroendocrine thymic tumours. Staging (Masaoka) included 483 (67%) stage I and II, 100 (14%) stage III and 70 (10%) stage IV tumours. The new International Association for the Study of Lung Cancer/International Thymic Malignancies Interest Group tumour, node and metastasis (TNM) classification was available for 224 patients and including 177 (85%) stage I–II, 37 (16%) stage IIIA and 10 (4%) stage IIIB tumours. Chemotherapy as induction and adjuvant treatment was used in 14% and 15% of the patients. Radiotherapy was almost exclusively used postoperatively (24%). A minimally invasive surgical approach (video-assisted thoracic surgery/robotic-assisted thoracic surgery) was used in 276 (33%) patients. The overall recurrence rate was 10.8% ( N  = 38). Compared to the ESTS retrospective database, the increased prevalence of thymic carcinomas (from 9% to 28%) and neuroendocrine thymic tumours (from 2% to 7%), an increase in the use of minimally invasive techniques (from 6% to 34%) and a wider use of chemotherapy as induction (from 9% to 15%) and adjuvant (from 2% to 16%) treatment were observed in the prospective database. The introduction of a set of variables considered essential for the data use ('minimum dataset') resulted in an increased average completeness rate. CONCLUSIONS: The reported data from the ESTS prospective thymic database confirm the recent trends in the management of thymic tumours. The ESTS prospective thymic database represents a powerful resource open to all ESTS members for the global effort to manage these rare tumours.